A Bánság, mint a történelmi Magyarország sajátos régiója különböző szemléletek tükrében - Kókai, Sándor (Közép-Európai Közlemények, 2010)
Todays the Bánság region maybe born again. There are a new form of the organization. There are looking for a place of the new globalization world. They are ready to work together their neighbours. Especially because the Hungary and Romanian there are member of the European Union. They are looking for all the connection system which was very strong on the historical time. They can only this way for them for the development way and the because there are difference kind of ethnics they can get helping by this way. After the Trianon treatment it is changed many economical and other problems and cut it down the traditional, economical and social connections.